0.04 degree-per-hour MEMS disk resonator gyroscope with high-quality factor (510 k) and long decaying time constant (74.9 s). (December 2018) - Li, Qingsong; Xiao, Dingbang; Zhou, Xin; Xu, Yi; Zhuo, Ming; Hou, Zhanqiang; He, Kaixuan; Zhang, Yongmeng; Wu, Xuezhong
Abstract The disk resonator gyroscope is an attractive candidate for high-performance MEMS gyroscopes. This gyroscope consists of a sensor and readout electronics, and the characteristics of the sensor directly determine the performance. For the sensor, a high-quality factor and long decaying time constant are the most important characteristics required to achieve high performance. We report a disk resonator gyroscope with a measured quality factor of 510 k and decaying time constant of 74.9 s, which is a record for MEMS silicon disk resonator gyroscopes, to the best of our knowledge. To improve the quality factor of the DRG, the quality factor improvement mechanism is first analyzed, and based on this mechanism two stiffness-mass decoupled methods, i.e., spoke length distribution optimization and lumped mass configuration design, are proposed and demonstrated. A disk resonator gyroscope prototype is fabricated based on these design strategies, and the sensor itself shows an angle random walk as low as 0.001°/√h, demonstrating true potential to achieve navigation-grade performance. The gyroscope with readout electronics shows an angle random walk of 0.01°/√h and a bias instability of 0.04°/h at room temperature without compensation, revealing that the performance of the gyroscope is severely limited by the readout electronics, which should be further improved. We expect that the quality factor improvement methods can be used in the design of other MEMS gyroscopes and that the newly designed DRG can be further improved to achieve navigation-grade performances for high-end industrial, transportation, aerospace, and automotive applications. MEMS: high-quality factor sensors for resonator gyroscopes A disk resonator gyroscope demonstrates a high-quality factor of 510 k and decay time constant of 74.9 s. High-performance MEMS gyroscopes are in demand for a range of high-end applications. Disk resonator gyroscopes are particularly promising candidates due to inherent mode matching and high thermal stability. However, many applications demand high-quality factors and long decay times. Now, a team led by Xuezhong Wu at the National University of Defense Technology, China, reports what they claim are record quality factors and decay times for MEMS silicon disk gyroscopes. Two mechanisms for stiffness-mass decoupling are attributed to the high performance, which the authors say could be used for the design of other MEMS gyroscopes.